Identification of dominant peptide epitopes and antibody response to the spike protein of SARS-CoV-2 - Zhang, Xianyan; Xu, Peipei; Xiao, Ting; Wang, Xinlu; Guo, Xuemin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveMultiple antigenic epitopes are present in the spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but they exhibit significant variation in immunogenicity and reactogenicity. We aimed to investigate the reactivity of different SARS-CoV-2 antigenic epitopes with serum antibodies from patients with COVID-19 and vaccinated individuals to characterize specific antibody responses.MethodsLinear B-cell peptides derived from the SARS-CoV-2 S protein were screened using the Immune Epitope Database (IEDB). These linear peptides were coupled to bovine serum albumin (BSA), and blot hybridization was used to investigate antigen–antibody reactions among the peptides, commercial anti-S protein polyclonal antibodies, and sera derived from vaccinated individuals and those with confirmed COVID-19. Sera from unvaccinated patients and BSA served as controls.ResultsSix linear B-cell peptide epitopes were identified from the IEDB and designated as P1–P6. Among these, P6 (aa 809–826) demonstrated stronger reactivity with rabbit anti-SARS-CoV-2 S polyclonal antibodies than the others. Antibodies against P2 (aa 553–570) were detected in the early stages of infection in four patients with confirmed COVID-19, and two of them developed antibodies against P5 (aa 601–640) later during the middle or late stages. Antibody responses against P1 (aa 209–226), P3 (aa 769–786), P4 (aa 287–317), and P6 were either extremely weak or undetected in patients with confirmed COVID-19. Sera from 45 individuals immunized with the inactivated vaccine were tested for reactivity against the six peptides. Antibody signals against P2, P5, and P6 were detected either individually or in combination, with P2 showing the highest frequency, followed by P6 and P5. Antibodies against P1, P3, and P4 were not detected. Six predicted B-cell dominant peptides exhibited distinct immunogenicity and reactogenicity, with P2 (aa 553–570) eliciting the strongest response. Antibody profiles against S protein epitopes differed between individuals infected with SARS-CoV-2 and those vaccinated with inactivated vaccines.ConclusionThe peptide combination of P2, P5, and P6 shows potential for the development of peptide-based target antigens for SARS-CoV-2 serological antibody diagnostic reagents, and reveals the response patterns of antibodies against SARS-CoV-2.